Collusion in mixed oligopolies and the coordinated effects of privatization - Correia-da-Silva, João (2019)
We study the sustainability of collusion in mixed oligopolies where private and public firms only differ in their objective: private firms maximize profits, while public firms maximize total surplus. If marginal costs are increasing, public firms do not supply the entire market, leaving room for private firms to produce and possibly cooperate by restricting output. The presence of public firms makes collusion among private firms harder to sustain, and maybe even unprofitable. As the number of private firms increases, collusion may become easier or harder to sustain. Privatization makes collusion easier to sustain, and is socially detrimental whenever firms are able to collude after privatization (which is always the case if they are sufficiently patient). Coordinated effects thus reverse the traditional result according to which privatization is socially desirable if there are many firms in the industry.